A case of Psoriasis with an increase in HDL cholesterol (Bangladesh Journal of Medical Science, 2014)
Psoriasis is an immune mediated chronic skin infection which is often associated with an abnormal lipid metabolism. Studies have proved that the abnormality in lipid profile is manifested by an increase in total cholesterol, LDL and VLDL cholesterol and a decrease in HDL cholesterol. The present case of psoriasis presents with an increased HDL cholesterol. Various studies have shown the alteration in size and number of HDL lipoproteins in psoriasis which hampers the normal efflux function of HDL lipoproteins. These HDL also have a significant alteration in protein and lipid content. These small and altered HDLs are more atherogenic and thereby increase the risk of cardiovascular diseases in such psoriatic patients. DOI: http://dx.doi.org/10.3329/bjms.v13i4.16261 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.470-472